2017
DOI: 10.1039/c6py01936f
|View full text |Cite
|
Sign up to set email alerts
|

Cobaltocenium-containing polybenzimidazole polymers for alkaline anion exchange membrane applications

Abstract: A novel cobaltocenium-containing polybenzimidazole polymer was used for alkaline anion exchange membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 42 publications
0
65
0
Order By: Relevance
“…[8] As shown in Figure S3, there is negligible change in characteristic UV absorption corresponding to cobaltocenium after it was dissolved in asolution of NaOH (pH 14) or HCl (pH 1.5) for two weeks.M oreover,p ublished work by Yan [9] and Zhu [10] both demonstrated that cobaltocenium cations with substituent group in Cp ring had superior thermal and chemical stability over other reported cations.S uch extraordinary stability of cationic cobaltocenium motivated us to design ultrastable polyelectrolytes in both cations and other compositions of frameworks for AEMs.T oc onstruct the new polymeric systems,w en eed to avoid the integration of functional groups (e.g.e ster,a mide,a nhydride,c arbonate) and linkers that are susceptible to degradation under strong basic conditions for ap rolonged period of time.D ue to the instabilities of ester or imide group,m ost cobaltocenium polymers reported in literature could not be used as stable AEMs directly. [8] As shown in Figure S3, there is negligible change in characteristic UV absorption corresponding to cobaltocenium after it was dissolved in asolution of NaOH (pH 14) or HCl (pH 1.5) for two weeks.M oreover,p ublished work by Yan [9] and Zhu [10] both demonstrated that cobaltocenium cations with substituent group in Cp ring had superior thermal and chemical stability over other reported cations.S uch extraordinary stability of cationic cobaltocenium motivated us to design ultrastable polyelectrolytes in both cations and other compositions of frameworks for AEMs.T oc onstruct the new polymeric systems,w en eed to avoid the integration of functional groups (e.g.e ster,a mide,a nhydride,c arbonate) and linkers that are susceptible to degradation under strong basic conditions for ap rolonged period of time.D ue to the instabilities of ester or imide group,m ost cobaltocenium polymers reported in literature could not be used as stable AEMs directly.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[8] As shown in Figure S3, there is negligible change in characteristic UV absorption corresponding to cobaltocenium after it was dissolved in asolution of NaOH (pH 14) or HCl (pH 1.5) for two weeks.M oreover,p ublished work by Yan [9] and Zhu [10] both demonstrated that cobaltocenium cations with substituent group in Cp ring had superior thermal and chemical stability over other reported cations.S uch extraordinary stability of cationic cobaltocenium motivated us to design ultrastable polyelectrolytes in both cations and other compositions of frameworks for AEMs.T oc onstruct the new polymeric systems,w en eed to avoid the integration of functional groups (e.g.e ster,a mide,a nhydride,c arbonate) and linkers that are susceptible to degradation under strong basic conditions for ap rolonged period of time.D ue to the instabilities of ester or imide group,m ost cobaltocenium polymers reported in literature could not be used as stable AEMs directly. [8] As shown in Figure S3, there is negligible change in characteristic UV absorption corresponding to cobaltocenium after it was dissolved in asolution of NaOH (pH 14) or HCl (pH 1.5) for two weeks.M oreover,p ublished work by Yan [9] and Zhu [10] both demonstrated that cobaltocenium cations with substituent group in Cp ring had superior thermal and chemical stability over other reported cations.S uch extraordinary stability of cationic cobaltocenium motivated us to design ultrastable polyelectrolytes in both cations and other compositions of frameworks for AEMs.T oc onstruct the new polymeric systems,w en eed to avoid the integration of functional groups (e.g.e ster,a mide,a nhydride,c arbonate) and linkers that are susceptible to degradation under strong basic conditions for ap rolonged period of time.D ue to the instabilities of ester or imide group,m ost cobaltocenium polymers reported in literature could not be used as stable AEMs directly.…”
mentioning
confidence: 99%
“…[2l] These membranes exhibited good ion conductivity and mechanical properties.H owever,t he decline of conductivity in alkaline condition over al ong term was ac oncern. [10] These membranes showed improved thermal stability and ion-exchange capacity,b ut the mechanical and alkaline stability of these AEMs were inferior because of the poor stability of linkage groups and the rigid polymer backbones.Both approaches adopted condensation polymerization to prepare rigid polymers with relatively limited molecular weight. [9] Theion conductivity was mediocre,partially due to the steric hindrance for the pentamethyl group.T hese polymers were quite brittle with elongation at break only about 10 %.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…AEMs, however, have two main drawbacks: (1) poor conductivity, as the anions typically have slower mobility than protons, and (2) low chemical stability, as the cation often used, quaternary ammonium, degrades in alkaline conditions . In addition, as the ion exchange capacity (IEC) of the material is increased, in an effort to improve conductivity, the water content also increases, often prompting a sharp decline in the mechanical stability …”
Section: Introductionmentioning
confidence: 99%